Glycerol‐K2CO3 Deep Eutectic Solvent as Environmentally Friendly Media with Basic and Dehumidifier Synergistic Effect for Running of Willgerodt‐Kindler Reaction. Issue 11 (23rd March 2018) - Radfar, Iman; Abbasi, Sepideh; Miraki, Maryam Kazemi; Yazdani, Elahe; Karimi, Meghdad; Heydari, Akbar
Abstract: In this report, a different green method of thioamidation promoted an almost quitted procedure: Willgerodt‐Kindler ( W‐K ) reaction. In order to eliminate the major problems in the W‐K process: H2 S releasing and also high‐temperature condition, a known Deep Eutectic Solvent (DES) exhibited a solution for such concerns. Use of Glycerol‐K2 CO3 as a DES (Gly‐K2 CO3 DES; 10:1 (mL: mmol)) is respect to its basic besides dehumidifying nature. Our next focus dedicated to the synthesis of new derivatives by altering acetophenone (as an alkyl aryl ketones) and secondary‐type amines. The efficient and optimized circumstances were assigned 30 min to 5 hours for reaction time and at 80°C to 100°C led to 71–88% yields for final thioamides. Abstract : Glycerol‐K2 CO3 as a DES due to its basic besides dehumidifying nature promoted Willgerodt‐Kindler ( W‐K ) reaction. The major problems in the W‐K process: H2 S releasing and also high‐temperature condition was removed using Glycerol‐K2 CO3 . The short time and good to excellent yields are advantage from this protocol.